Assessment of Lower Limb Muscle Volume Using 3D Ultrasonography: Validity and Reliability Compared to MRI - Paul Ritsche; Romina Ledergerber; Michele Pansini; Francesco Santini; Oliver Faude (Current Issues in Sport Science)
Introduction Muscle volume is a crucial indicator of muscle strength and neuromuscular health, traditionally assessed using Magnetic Resonance Imaging (MRI). While MRI provides high accuracy, it is costly and time-consuming. Three-dimensional ultrasonography (3DUS) offers a more accessible alternative but requires rigorous validation due to setup dependent accuracy. This study evaluates the validity and reliability of a custom 3DUS setup for measuring lower limb muscle volumes, compares it to MRI, and documents the methodology for broader research adoption.